Ouabain Binding and Cation Transport in Human Erythrocytes - Gardner, Jerry D. (1973)
In the present studies we have explored the relation between ouabain binding and the inhibition of potassium influx in intact human erythrocytes. The rate at which bound ouabain molecules dissociate from the erythrocyte membrane is not altered by complete replacement of choline with sodium or by partial replacement with potassium. These findings indicate that the effects of these cations on ouabain binding reflect alterations in the rate of association of ouabain molecules with the erythrocyte membrane. Variations in the cation composition of the incubation solution did not alter the relation between the fraction of the glycosidebinding sites occupied by ouabain or the fraction of ouabain-sensitive potassium influx which was inhibited. That is, irrespective of the affinity of the erythrocyte membrane for ouabain molecules and irrespective of the magnitude of glycoside-sensitive potassium influx, occupation of a given fraction of the glycoside-binding sites by ouabain results in the inhibition of an equal fraction of the ouabain-sensitive potassium transport sites.